Euphemism and dysphemism expression in “The Rainbow Troops” novel by Andrea Hirata - Malikhatul Lailiyah; Karlina Karadila Yustisia (Universitas Merdeka Malang, 2018)
This study analyses the used of euphemism and dysphemism in the Indonesian novel which is translated into English. The purpose of this study to find and to explain the used of those terms in the Rainbow Troops Novel by Andrea Hirata. In analysing, descriptive qualitative is used. The data collected through documentation and corpuses. The research revealed that there are a lot of forms and styles in the used of these two expressions. Moreover, this analysis has explained why people speech differently in different social context and by identifying the social function of social language and the way it is used to convey social meaning. DOI: 10.26905/enjourme.v3i2.3045